Anthropometric and dietary indicators applied in population-based surveys: a systematic review (Research, Society and Development, 2022)
Aim: To identify population-based health and nutrition surveys, conducted with adults and the elderly, and performed in the Americas, Europe, and Oceania, to investigate the more common anthropometric and food consumption methods used, their applicability, and their limitations. Methods: Electronic databases (LILACS, PubMed, and SCOPUS) were systematically searched for studies published between 1997 and 2017 in Portuguese, English, or Spanish. 48 studies (45.8% carried out in the Americas) met the eligibility criteria and were included in the review. The data were analyzed in 2018.  Results: The methodological quality of most of the studies (64.4%) was classified as moderate, according to the Agency for Healthcare Research and Quality checklist for cross-sectional studies and the Newcastle-Ottawa scale for cohort studies. 35.4% of the articles evaluated only food consumption, 29.2% just anthropometry, while 35.4% evaluated food consumption and anthropometric measurements. The most used food survey methods were food record (31% of studies) and the 24-hour dietary recall (22% of studies). Body mass index (BMI) was the most used indicator for anthropometric nutritional status assessment. Although most of the studies used the World Health Organization classification criteria, these studies did not adopt the different cut-off points for BMI classification for adults and the elderly.  Conclusion: BMI and methods that record current consumption, such as the food record and the 24-hour dietary recall, were the main methods of assessing nutritional status, taking into consideration the easy application, low cost, and good reproducibility. Systematic Review Registration: PROSPEROCRD42017071392.